Synthesis of Reactivity of Mixed Ligand Copper(II) Complexes - Balasubramanian, V.; Muthukumaran, S.; Rosekumari, I.; Lilly, K.O.; Karthikeyan, N. (Asian Journal of Chemistry, 2010)
A series of paramagnetic mixed ligand copper(II) complexe, CuAB, where A = salicylaldehyde and B = β-diketone/β-ketoimine are subjected to phenylisocyanation, α-naphthylisocyanation, nitrosation and diamine condensation reactions. Phenylisocyanate and α-naphthylisocyanate attack the γ-CH of β-diketone/-ketoimine moiety and after prototropic rearrangement form amido derivatives. The results are presented based on spectroscopic results. The structure of the chelates is proposed.